Diagnostic Role of Prostate-Specific Membrane Antigen in Adrenocortical Carcinoma - Gu, Yulin; Gu, Weijun; Dou, Jingtao; Lu, Zhaohui; Ba, Jianming; Li, Jie; Wang, Xiaocong; Liu, Hongyan; Yang, Guoqing; Guo, Qinghua; Zang, Li; Chen, Kang; et al. (Frontiers in Endocrinology, 2019)
Objective: To investigate the role of PSMA in the differential diagnosis of adrenocortical carcinoma samples (ACCs) and adrenocortical adenoma samples (ACAs), to validate the prognostic role of PSMA in patients with ACCs, and to explore the possibility that this marker can differentiate localized ACCs from adrenal metastases from other sites. Methods: PSMA protein expression in tissue samples from 50 ACCs, 90 ACAs (including 20 from patients who presented with Cushing's syndrome, 20 aldosterone-producing adenomas and 50 non-functional tumors) and 10 tissues that were metastases from other primary sites was assessed by immunohistochemistry. The clinical and pathological characteristics were compared, the intensity and density were analyzed, and the prognostic role was evaluated. Results: The analysis of clinical and pathological features revealed that the size of ACCs was greater than that of benign tissues and the ACC patients were older than the ACA patients (p < 0.01). The percentage of PSMA-positive vessels, the mean intensity and the degree of staining density were found to be significantly lower in ACAs than in ACCs (p < 0.01). In these 140 samples, 60% of the ACCs were grouped in the positive category. The samples were negative for metastases that were from other primary sites. The ENSAT stage and Ki-67 were correlated with PSMA expression. The survival distribution revealed that high PSMA expression did not show any prognostic relevance in the current ACCs series. Those samples with a score of > 3.5 were 75 times more likely to be malignant (OR = 75). We established a cut-off score of 3.5 (p < 0.05), which had 46% sensitivity and 99% specificity. Paralleling PSMA and Ki-67 maximized the area under the curve, with 72% sensitivity and 100% specificity. Conclusions: Our results strongly confirm that PSMA is helpful for distinguishing benign from malignant tumors and that its high expression levels correlate with a high ENSAT stage and high proliferation. The combination of PSMA and Ki-67 can be particularly useful. Furthermore, PSMA might be a useful tool for the identification of localized adrenal carcinoma and metastatic carcinoma.